2017
DOI: 10.1161/hypertensionaha.117.09023
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory Pulse Wave Velocity Is a Stronger Predictor of Cardiovascular Events and All-Cause Mortality Than Office and Ambulatory Blood Pressure in Hemodialysis Patients

Abstract: Arterial stiffness and augmentation of aortic blood pressure (BP) measured in office are known cardiovascular risk factors in hemodialysis patients. This study examines the prognostic significance of ambulatory brachial BP, central BP, pulse wave velocity (PWV), and heart rate–adjusted augmentation index [AIx(75)] in this population. A total of 170 hemodialysis patients underwent 48-hour ambulatory monitoring with Mobil-O-Graph-NG during a standard interdialytic interval and followed-up for 28.1±11.2 months. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
83
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(88 citation statements)
references
References 48 publications
3
83
1
1
Order By: Relevance
“…Over a mean follow-up of 50 months, surviving patients were characterized by simultaneous decrease in aortic PWV and BP, that is, “pressure-dependent stiffness.” In non-survivors, despite a similar reduction in BP, the aortic PWV steadily increased, that is, “pressure-independent stiffening.” This observation suggested the hypothesis that modification of arterial stiffness and not BP could be the risk factor associated with the prognosis and outcomes. The recent study by Sarafidis et al [19] supports this hypothesis. In hemodialysis patients, authors compared the value of 48-h ambulatory BP (brachial and central) and 48-h aortic PWV measures for major cardiovascular outcomes and all-cause mortality.…”
Section: Arterial Stiffness In End-stage Renal Disease (Chronic Kidnementioning
confidence: 73%
See 2 more Smart Citations
“…Over a mean follow-up of 50 months, surviving patients were characterized by simultaneous decrease in aortic PWV and BP, that is, “pressure-dependent stiffness.” In non-survivors, despite a similar reduction in BP, the aortic PWV steadily increased, that is, “pressure-independent stiffening.” This observation suggested the hypothesis that modification of arterial stiffness and not BP could be the risk factor associated with the prognosis and outcomes. The recent study by Sarafidis et al [19] supports this hypothesis. In hemodialysis patients, authors compared the value of 48-h ambulatory BP (brachial and central) and 48-h aortic PWV measures for major cardiovascular outcomes and all-cause mortality.…”
Section: Arterial Stiffness In End-stage Renal Disease (Chronic Kidnementioning
confidence: 73%
“…Premature vascular aging and arterial stiffening are observed with the progression of CKD [16-18]. The most characteristic arterial change observed is the arterial stiffening, more pronounced in the aorta than in peripheral arteries [6, 19]. This condition is responsible for the reduction of the arterial stiffness gradient and impedance mismatch with diminished capacity to lower pulsatile pressure transmission to the peripheral microcirculation [8, 15].…”
Section: Arterial Stiffness In End-stage Renal Disease (Chronic Kidnementioning
confidence: 99%
See 1 more Smart Citation
“…Although recent studies could not reproduce a predictive value of predialytic Office-PWV in elderly patients with ESRD [18,19], another study suggested an association of ambulatory 48-hour PWV with cardiovascular events and death in hemodialysis [20]. This discrepancy might be due to methodological issues.…”
Section: Introductionmentioning
confidence: 93%
“…For this reason, the need to improve current techniques or biomarkers for the assessment of vascular properties has led to new concepts and approaches. One step forward is achieved by the ambulatory monitoring of arterial stiffness, which was proven in the study of Sarafidis et al 7 to be superior for the prediction of cardiovascular events and allcause mortality in hemodialysis patients compared with traditional hemodynamic measures. Another step forward might be the assessment of total arterial compliance instead of indices measuring local or segmental arterial properties.…”
Section: See Related Article Pp 148-157mentioning
confidence: 99%